2016
DOI: 10.1016/j.euromechflu.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydrodynamics of a moving trawl codend and its fluttering motions in flume tank

Abstract: The coupled dynamics of the codend fluttering motion and its hydrodynamics behavior are investigated based on PIV measurements carried out around a 1/10 scaled model codend. The mean wake flow characteristics are firstly analyzed demonstrating the great effect of the codend motion. The differences in flow contour between fluttering motion and no-fluttering codend are highlighted by analyzing the classical mean characteristics of a body wake flow. In presence of fluttering motion, the classical results are reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
9
18
2
Order By: Relevance
“…The experimental apparatus effect of model nets is a common problem, especially in codend model tests. This study and previous studies by Pichot et al [24], Bouhoubeiny et al [14], and Druault and Germain [13] used a self-designed configuration of this rigid frame to accurately measure the hydrodynamic forces of the codend. One of the principal objectives in fishing gear hydrodynamic measurements is to design frames with very lower drag forces unlike those of fishing equipment in general, and nettings or codends in particular.…”
Section: Effect Of Rigid Frame Drag Force On Codendmentioning
confidence: 89%
See 4 more Smart Citations
“…The experimental apparatus effect of model nets is a common problem, especially in codend model tests. This study and previous studies by Pichot et al [24], Bouhoubeiny et al [14], and Druault and Germain [13] used a self-designed configuration of this rigid frame to accurately measure the hydrodynamic forces of the codend. One of the principal objectives in fishing gear hydrodynamic measurements is to design frames with very lower drag forces unlike those of fishing equipment in general, and nettings or codends in particular.…”
Section: Effect Of Rigid Frame Drag Force On Codendmentioning
confidence: 89%
“…A codend with catch has obvious oscillations in position or drag force. Previously, Bouhoubeiny et al [14], Madsen et al [18], and Druault and Germain [13] reported that codend oscillations can be caused by the vortices behind the codend. When dragging the trawl, vortex shedding generates vertical pressure on the codend and makes it oscillate.…”
Section: Effect Of Cutting Ratio On the Shape And Drag Force Oscillation Of Codends With Catchmentioning
confidence: 99%
See 3 more Smart Citations